2015
DOI: 10.1016/j.biotri.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Adverse condition testing with hip simulators

Abstract: Recent clinical failures and abnormal sounds observed in certain prosthetic hip designs have directed attention to adverse condition hip simulator testing. In the present study, hip simulator wear and friction tests were made with a macroscopic separation of the bearing surfaces in the swing phase, steep acetabular cup position, increased load, poor or lacking lubrication, roughened bearing surfaces including titanium third bodies, and with combinations of these. The only conditions that resulted in squeaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Above the limit the tribological behaviour of the device is unacceptable, i.e., wear and friction will inevitably -not only occasionally -be so high that serious damage to the patient and early failure of the arthroplasty would result. Well below the limit, the wear and its variation are low [1][2][3]. In the present study, the limit was being approached with a combination of 2 kN peak load and 70° inclination angle.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…Above the limit the tribological behaviour of the device is unacceptable, i.e., wear and friction will inevitably -not only occasionally -be so high that serious damage to the patient and early failure of the arthroplasty would result. Well below the limit, the wear and its variation are low [1][2][3]. In the present study, the limit was being approached with a combination of 2 kN peak load and 70° inclination angle.…”
Section: Introductionmentioning
confidence: 56%
“…In an earlier study, high variation in wear was observed in the 52 mm diameter Metasul MoM (n = 3) with an optimal inclination of the cup, 48°, and a very high peak load of 4 kN [3]. Loud squeak was produced by the prosthesis with the highest wear rate of 116 mg/10 6 cycles.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations